1994
DOI: 10.3168/jds.s0022-0302(94)77251-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Status of Dairy Cows Supplemented Prepartum with Vitamin E and Selenium

Abstract: Possible relationships among dietary antioxidants, oxidative status, and placental retention were investigated in periparturient dairy cows. During 6 wk prepartum, 16 cows each were given daily by capsule 1000 IU of vitamin E, 3 mg of Se, both vitamin E and Se, or neither (control). alpha-Tocopherol in serum and fast-acting antioxidants in plasma increased, but, in red blood cells, thiobarbituric acid-reactive substances decreased during the last 6 wk before parturition in cows given vitamin E. These measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 12 publications
4
65
0
2
Order By: Relevance
“…According to Miller et al (1993), improper feeding and antioxidant deficiencies in the ration during the transition period contribute to reduced muscle tension, which leads to placenta retention. According to Brzezińska-Ślebodzińska et al (1994), deficiency of vitamin E and selenium in the last weeks of pregnancy increases the production of lipid peroxide, and thus the frequency of retained placenta and postpartum metritis. The oxidant-antioxidant imbalance may also contribute to sexual cycle disorders.…”
Section: Oxidative Stress In Ruminantsmentioning
confidence: 99%
“…According to Miller et al (1993), improper feeding and antioxidant deficiencies in the ration during the transition period contribute to reduced muscle tension, which leads to placenta retention. According to Brzezińska-Ślebodzińska et al (1994), deficiency of vitamin E and selenium in the last weeks of pregnancy increases the production of lipid peroxide, and thus the frequency of retained placenta and postpartum metritis. The oxidant-antioxidant imbalance may also contribute to sexual cycle disorders.…”
Section: Oxidative Stress In Ruminantsmentioning
confidence: 99%
“…Abuelo et al (2014) recently provided a review of the in vivo benefits of dietary antioxidants on udder health, uterine health and reproductive performance, and incidence of production diseases of periparturient cows. Insufficient dietary antioxidants during this period were suggested to possibly increase oxidative stress and occurrence of retained placenta in dairy cows (Brzezinska-Slebodzinska et al, 1994). However, supplementing transition cows and periparturient heifers with vitamin E resulted in improved signs of oxidative status with regards to higher serum α-tocopherol level, decreased lipid peroxidation and reduced oxidative damage in liver (Brzezinska-Slebodzinska et al, 1994;Bouwstra et al, 2008 and2009).…”
Section: Ruminantsmentioning
confidence: 99%
“…Insufficient dietary antioxidants during this period were suggested to possibly increase oxidative stress and occurrence of retained placenta in dairy cows (Brzezinska-Slebodzinska et al, 1994). However, supplementing transition cows and periparturient heifers with vitamin E resulted in improved signs of oxidative status with regards to higher serum α-tocopherol level, decreased lipid peroxidation and reduced oxidative damage in liver (Brzezinska-Slebodzinska et al, 1994;Bouwstra et al, 2008 and2009). A meta-analysis of 19 experiments suggested that dietary addition of vitamin E and Se could decrease the average relative risk of mastitis by 34% (Zeiler et al, 2010).…”
Section: Ruminantsmentioning
confidence: 99%
“…Another reason for the oxidative stress to arise in pregnancy is depletion of antioxidant reserves and preparation for lactation (Miller and BrzezinskaSlebodzinska, 1993). All these changes are a result of physiologic adaptation caused by cows being in need of energy during pregnancy (Miller and BrzezinskaSlebodzinska 1993;Brzezinska-Slebodzinska et al, 1994;Stec et al, 1991). During the pregnancy and lactation periods of cows, many studies are conveyed about increasing PON-1 activities on retained fetal membrane (RFM), severe birth and liver hypertrophy (Turk et al, 2004;Bademkıran et al, 2008).…”
Section: Introductionmentioning
confidence: 99%